The Role of Study Visit in Learning, Motivation, and Intercultural Understanding of German Literature Students - Ardine, Kamila Adriana; Khalishah, Nur Waiduri; Anavi, Wilma Prisca; Sobara, Iwa (Nexus Publishing NXP, 2025)
This research analyzes the role of study visits to Germany on language learning, motivation, and intercultural understanding of German Literature students at State University of Malang. A qualitative method with a phenomenological approach was used to explore the experiences of program participants. The results show that the 10-day program strengthens learning motivation through direct exposure to German culture and academic environment, encourages reflection, and changes learning strategies. According to Kolb's Experiential Learning theory, participants experienced all stages of experiential learning, which strengthened their cultural awareness, language confidence, and career goals in international contexts.